Pengaruh Tingkat Literasi Digital terhadap Produktivitas Tenaga Pendidik: Penelitian - Fauziah Nur; Catra Indra Cahyadi; Rossi Peter Simanjuntak; Achmad Chair (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the influence of digital literacy levels on the productivity of educators at the Medan Aviation Polytechnic, considering the demands of technological developments in the Society 5.0 era that require educators to master various digital skills to support the Tridharma of Higher Education. Using a quantitative descriptive method through a survey of 50 educator respondents (total sampling), this study measures four pillars of digital literacy: Digital Skills, Digital Ethics, Digital Safety, and Digital Culture. The results show that the four dimensions of digital literacy have a significant and positive influence on educator productivity (p-value 0.000 < 0.05). Specifically, Digital Culture is the variable that has the greatest influence, with a tendency of 49-fold influence on increasing educator productivity at the institution.